1995
DOI: 10.1021/bi00009a004
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of NADH-Cytochrome b5 Reductase from Pig Liver at 2.4 .ANG. Resolution

Abstract: The three-dimensional structure of NADH-cytochrome b5 reductase from pig liver microsomes has been determined at 2.4 A resolution by X-ray crystallography. The molecular structure reveals two domains, the FAD binding domain and the NADH domain. A large cleft lies between these two domains and contains the binding site for the FAD prosthetic group. The backbone structure of the FAD binding domain has a great similarity to that of ferredoxin-NADP+ reductase [Karplus, P. A., Daniels, M. J., & Herriott, J. R. (199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 26 publications
3
69
0
Order By: Relevance
“…with other members of the ferredoxin reductase family of enzymes, including spinach ferredoxin-NADP + oxidoreductase (FNR) [10], corn nitrate reductase [11] and porcine cytochrome b & reductase [12]. The FLDR structure reveals an unusual flavinbinding conformation, with a hydrogen bond between the adenine and isoalloxazine rings, possibly explaining the unusual visible spectrum of the bound flavin [7].…”
Section: Introductionmentioning
confidence: 99%
“…with other members of the ferredoxin reductase family of enzymes, including spinach ferredoxin-NADP + oxidoreductase (FNR) [10], corn nitrate reductase [11] and porcine cytochrome b & reductase [12]. The FLDR structure reveals an unusual flavinbinding conformation, with a hydrogen bond between the adenine and isoalloxazine rings, possibly explaining the unusual visible spectrum of the bound flavin [7].…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary tertiary structure of human erythrocyte b5R (15,16), and the detailed tertiary structures of porcine and rat liver b5Rs at 2.1 Å resolution have been determined by x-ray crystallography (17)(18)(19)(20)(21). These structural studies revealed that NADH-cytochrome b 5 reductase belongs to the structurally related so-called "ferredoxin reductase family" (22,23) together with other flavoenzymes such as ferredoxin-NADP ϩ oxidoreductase (FNR) (22), phthalate dioxygenase reductase (24), flavodoxin reductase (25), NADPH-cytochrome P-450 reductase (26), and the cytochrome b reductase domain of nitrate reductase (27).…”
mentioning
confidence: 99%
“…The molecule of NADH-cytochrome b5 reductase is composed of two domains, the FAD binding domain (residues 2-118) and the NADH domain (residues 119-272) (Nishida et al, 1995). The highest scored docking pose for inhibitors (luteolin, quercetin and taxifolin) revealed that all the inhibitors occupied the NADH binding domain (Fig 1).…”
Section: Resultsmentioning
confidence: 99%